Finding online social support among members of Philippine political supporter groups on Facebook - Asombrado, Angelica E.; Cañete, Gessa S.; Dacaymat, Jules Larence P.; Pangilinan, Francine Therese Q.
This study looked into the influence of online group membership among Philippine political supporter groups on Facebook through the dimensions of Cullen and Drennon-Gala's Social Support Theory. It also explored the members' experiences of giving and receiving social support within the group during and after the 2022 National Elections, as related literature has shown that participating in online political discussions are said to make an individual feel supported by others; satisfying our desire for social identification and connection which positively affects our psychological health. Semi-structured interviews were then conducted among ten (10) participants to gather in-depth insights that would help expound the use and practicality of these Facebook groups. Through thematic analysis, a total of seven (7) main themes were discovered, including the four (4) constructs of the Social Support Theory. It proves the usefulness of the groups and the presence of social support even in online settings, but it would mostly depend on how positive the interactions are and how active the members are in the group. Further studies about these Facebook groups and other online communities are recommended to expand the Social Support Theory within the online context.